2016
DOI: 10.1002/eet.1743
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Challenges in Environmental Governance: Technology, governance and the social licence

Abstract: The process through which societal actors can exert direct influence on the behaviour of organizations has gained increasing attention over the past two decades and is increasingly referred to as 'social licence' or 'social licence to operate'. This paper documents the rise of social licence and analyses the relationship between information and communication technology (ICT), governance and the social licence. We argue that contemporary social licence and the increasingly prominent role societal actors have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 71 publications
(123 reference statements)
0
18
0
1
Order By: Relevance
“…In recent years, industries as well as policy-making and research fields have become active in advancing CE. The growing acceptance of the CE concept may prove to be the next step for industry in gaining legitimacy for sustainability innovations and ensuring increasingly important social support [13] for corporate actors. CE is expected to become a mainstream business priority in the foreseeable future [14], affecting public-private relations and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, industries as well as policy-making and research fields have become active in advancing CE. The growing acceptance of the CE concept may prove to be the next step for industry in gaining legitimacy for sustainability innovations and ensuring increasingly important social support [13] for corporate actors. CE is expected to become a mainstream business priority in the foreseeable future [14], affecting public-private relations and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Social licence is a concept that may be used as a tool to incentivise the public to voice concerns on marine issues that may otherwise remain unnoticed or ignored (Cullen-Knox et al, 2016). To date, no consensus definition of the concept has been achieved however, we, in this paper, consider it "an unwritten social contract" (Moffat et al, 2015) that reflects broader community opinions and expectations on the impacts and benefits of industry and government practises, including research (Edwards and Lacey, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the group suggested that social licence is a balancing act between companies and communities. -Knox et al (2016) and Moffat et al (2016) note the changing dynamics of SLO, and thus perceptions of how communities are now defined-not solely in terms of local geography or proximity, but including more dispersed 'communities of interest' that may be globally distributed. Furthermore, the proliferation of information in the 'media age' through the Internet and social media creates new channels of information and avenues of influence between private industries and interested communities (Fraser 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Societal expectations about the environmental, social and cultural 'performance' of industries involved in the development, use or management of natural resources have changed over recent decades (Cullen-Knox et al 2016, Moffat et al 2016. This change is reflected in increasing expectations that communities will receive a greater share of the benefits from the presence of such industries along with assurances that these industries are appropriately regulated (Prno 2013, Van Putten et al 2018.…”
Section: Social Licence To Operatementioning
confidence: 99%